2023
DOI: 10.1111/all.15840
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy in alpha‐gal red meat allergy: Could specific IgE be a potential biomarker in monitoring management?

D. Ünal,
D. Eyice‐Karabacak,
A. Kutlu
et al.

Abstract: BackgroundOral immunotherapy (OIT) is a promising treatment for food allergies. Our aim was to establish the long‐term safety and efficacy of a novel red meat (RM) OIT in galactose‐alpha‐1,3‐galactose (alpha‐gal) allergy in adults.MethodsOut of 20 patients with confirmed RM allergy, five (41.66%) underwent an early OIT, seven (58.33%) underwent a delayed protocol and eight patients who were not desensitized formed the patient control group. 15 and 27 day RM OIT for early‐onset and delayed‐onset alpha‐gal aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…
We had read the article entitled "Oral immunotherapy in alphagal red meat allergy: Could specific IgE be a potential biomarker in monitoring management?" by D. Ünal et al 1 We appreciate the authors for this successful research and would like to point out some suggestions.Data sharing not applicable to this article as no datasets were generated or analysed during the current study.
…”
mentioning
confidence: 88%
“…
We had read the article entitled "Oral immunotherapy in alphagal red meat allergy: Could specific IgE be a potential biomarker in monitoring management?" by D. Ünal et al 1 We appreciate the authors for this successful research and would like to point out some suggestions.Data sharing not applicable to this article as no datasets were generated or analysed during the current study.
…”
mentioning
confidence: 88%
“…There is no cure for AGS. Recently, a small oral immunotherapy (OIT) study for early and delayed-onset red meat allergy was reported ( 173 ). Five patients underwent an early OIT and seven a delayed protocol and the patients were followed for up to five years.…”
Section: Managementmentioning
confidence: 99%
“…The patients should be informed about the relevance of tick bites on the onset of the disease and that further tick bites increase IgE levels to a-Gal, while avoidance of tick bites decreases their IgE levels to a-Gal. There are cases whose IgE levels to a-Gal became negative (or significantly dropped) after tick avoidance and they were able to reintroduce mammalian meat in their diet (115,163,172). AGS patients should wear long trousers and long-sleeved shirts in wooded and grassy areas and use insect repellents.…”
Section: Managementmentioning
confidence: 99%
“…153 A few case reports have suggested OIT may be safe and effective in AGS, which is supported by a recently published series of 12 cases that underwent successful OIT. [154][155][156]…”
Section: Iag Nos Is and Manag Ementmentioning
confidence: 99%